Lectura Crítica - Masapanta Masapanta, Jessica Fabiola (2016)
Critical reading comes from intellectual exercise that supposed to make inferences about the same, whether simple or complex; without free opinion of the reader, it is a medium in which the student develops vocabulary with greater intensity, becoming constructivist questioner autonomy of thought. In the School of General Education Basic "Francisco de Orellana" has found that students do not develop an adequate standard of reading, because teachers do not practice so efficient strategies critical reading or analytical in students, which does not achieve significant learning that foster language skills. The project took as a reference field information and literature, essential elements to establish guidelines for the research, which is supported in the deductive and inductive methods through surveys, for it an instrument for data collection was designed and back proposed development, training and implementation of a methodological guide strategies for the development of critical reading, which will positively contribute to the process of teaching - learning, encourage a love of reading and therefore the formation of the student; for this different educational software and other technological tools they will be used, which when used properly will favor the development of skills and competencies aimed at what the student should know, should know how and should be; with this would benefit 118 people who make up the educational community. From the foregoing, it is intended that the implementation of this pedagogical proposal allows all elementary school students of that school, appropriating significantly from readers techniques, which will encourage them to critically read any type of text, facilitating interpretation all literary content.